Assessing the Urgency of Government Regulation Number 28 of 2024 on Telemedicine and Digital Consumer Protection - Harinawantara, B. Hangga; Asfihani, Nadya Zhafira; Fikri, Ahmad Ma’mun (Research Horizon, 2025)
Government Regulation Number 28 of 2024 focuses on aligning health policies with consumer protection in the digital era, especially in the context of telemedicine. This study analyzes the urgency of this regulation amidst the development of information technology that has changed the delivery of health services. Telemedicine offers easy access, especially in remote areas, but is also faced with challenges related to service quality, data security, and protection of consumer rights. With a normative legal approach, this study evaluates the norms in the PP and their impact on digital health practices. The results show that technological infrastructure, health worker competence, and clear regulations are very important to ensure the effectiveness of telemedicine. In addition, personal data protection is a crucial issue that needs to be regulated to maintain consumer trust. Challenges in the consistency of service standards and digital literacy of the community were also identified. Therefore, collaboration between the government, health service providers, and the community is needed to build an efficient and effective telemedicine ecosystem, which in turn can improve the quality of health services in Indonesia. This study is expected to contribute to the development of relevant and comprehensive policies in the field of digital health.